Single or Double: Which Is the Altar of Atomic Catalysts for Nitrogen Reduction Reaction?. Issue 6 (4th October 2018) - Chen, Zhi Wen; Yan, Jun‐Min; Jiang, Qing
Abstract: Converting N2 to NH3 is an extremely valuable process but a long‐standing challenge in chemistry. The crux is the choice of catalysts, where single atomic catalysts (SAC) are always pursued as the altar of atomic catalysts. In this paper, double atomic catalysts (DAC) of TM2 ‐C2 N with SAC of TM‐C2 N (TM = Cr, Mn, Fe, Co, and Ni) for nitrogen reduction reaction (NRR) are systematically compared. Unexpectedly, TM2 ‐C2 N are more suitable than TM‐C2 N as catalysts for NRR. Moreover, the Mn2 ‐C2 N endows the highest catalytic activity with the lowest potential of −0.23 V versus RHE, which is the best among all reported calculation results for NRR under ambient conditions. As a result, a new way to design catalysts with DAC is provided. Abstract : Double atomic catalysts will become the altar of atomic catalysts for nitrogen reduction reaction instead of single atomic catalysts. Moreover, the Mn2 ‐C2 N has the highest catalytic activity with the potential of −0.23 V versus reversible hydrogen electrode, indicating the promising catalyst for practical applications.